Prenatal diagnosis of spontaneous twin anemia-polycythemia sequence and postnatal examination of placental vascular anastomoses - Bae, Jin Young (Obstet Gynecol Sci, 2016)
Twin anemia-polycythemia sequence (TAPS) is characterized by a wide discrepancy of hemoglobin between two monochorionic fetuses without sign of twin oligo-polyhydramnios sequence. A primiparous woman with monochorionic diamniotic twin transferred for preterm labor. Ultrasonographic evaluation at 32+3 weeks of gestation revealed increased middle cerebral artery-peak systolic velocity (77.4 cm/sec, 1.69 multiples of median) in donor and decreased in recipient twin (36.4 cm/sec, 0.79 multiples of median), the twin was diagnosed with TAPS. Repeated cesarean section was performed at 32+5 weeks of gestation following preeclampsia and preterm labor. After delivery, TAPS was confirmed through neonatal hematologic examination. There were no signs of acute hemorrhagic shock or brain injury. Placental evaluation via dye infusion and barium angiogram revealed one arterioarterial anastomoses with six arteriovenous anastomoses of placenta. We report a prenatally diagnosed case of spontaneous TAPS with arterioarterial and arteriovenous anastomoses and suggest careful monitoring of monochorionic twin and opinion on placenta vascular architecture.